Kartiranje lokalnih podnebnih območij Ljubljane - Gregorčič, Tim (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2025)
The Local Climate Zone (LCZ) framework was introduced to facilitate standardised research in the field of urban climate and other related scientific disciplines. This study presents the LCZ classification of Ljubljana, employing two methods: Cellular Automata and WUDAPT. Their effectiveness was evaluated by explaining spatial vari-ations in land surface temperature and canopy urban heat islands, as well as through expert judgement. The results of the WUDAPT method are considered more repre-sentative, thus providing a robust foundation for future urban climate research.
Keywords: cellular automata; local climate zones (LCZ); lokalna podnebna območja (LPO); mestno podnebje; metoda celičnega avtomata (CA); metoda WUDAPT; micrometeorological classification; mikrometeorološka klasifikacija; urban climate; WUDAPT